El arte como medio de reflexión del consumo de sustancias ilícitas en los adolescentes - Cacay Pulla, Leslie Lizbeth (Machala : Universidad Técnica de Machala, 2025)
This graduation Project explores art as a medium for social reflection, focusing on the issue of drug and alcohol use among teenagers, Looking for a shelter was created to express the emotions and realities faced by young people in vulnerable situations, influenced by difficult family dynamics and social pressure. The piece uses symbolic imagery and color to convey emotional tension, the creative process included stages of plaiting, production, and editing, using expressive techniques inspired by artistic movements like social realism and expressionism, in the final phase, key visual details were refined to enhance the work’s message. The project also analyzes how the painting communicates with its audience. Its visual impact invites reflection and opens dialogue about the subject matter, especially after being shared online. Reactions from viewers showed genuine engagement with the use of color and symbolic elements. This confirms the work's purpose: to raise awareness, spark meaningful thought, and encourage conversation about a critical issue affecting many teens.
Este trabajo de titulación explora el arte como medio de reflexión social, abordando el consumo de alcohol y drogas en adolescentes, la obra buscando un refugio nace del interés por representar las emociones y contextos que enfrentan jóvenes en situación vulnerable influenciado por entornos familiares fríos y presiones externas. Se concibe una pintura cargada de simbolismo y color, que transmite desde lo visual la tensión emocional del protagonista, el proceso creativo atravesó fase de preproducción, producción y edición final, empleando técnicas expresivas y referente visual ligados al realismo social y expresionismo y en la etapa final Se afinaron los elementos estéticos para reforzar el mensaje de crítica. Finalmente se analiza la recepción de la obra como herramienta de comunicación, el impacto visual provoca reflexión y diálogo con el espectador cumpliendo la función de visibilizar problemáticas reales que afectan a los adolescentes, confirmando que el arte además de expresar tiene el poder de concienciar y transformar.
Keywords: PINTURA; REFLEXIÓN; DROGAS; ALCOHOL